Requirement of n-6 and n-3 Fatty Acid in Broodstock Diets on Reproductive Performance of Green catfish, Hemibagrus nemurus Blkr. - Adharto Utiah; M. Zairin Junior; I. Mokoginta; R. Affandi; K. Sumantadinata (Jurnal Akuakultur Indonesia)
This experiment was conducted to determine the optimum dietary level of n-6 and n-3 fatty acids on reproduction performance of green catfish. Four experimental diets with different level of n-6 and n-3 fatty acid (diet A: 0.77% n-6 fatty acid, 0.07% n-3 fatty acid; diet B: 1.56%,0.10 %; diet C: 1.74%, 0.13 % and diet D: 2%, 0.28%) were used in this experiment during seven month. Diets given twice every day in the morning and evening. The 28 broodstock used in this research with density every waring seven broodstock. Samples of eggs were analyzed for fatty acid composition. The diameter of eggs, fecundity, hatching rate of the eggs, survival rate and percentage of abnormal larvae were determined. Results showed that different dietary level of n-6 and n-3 fatty acids of the broodstock significantly affect the reproductive performance especially fecundity and hatching rate of eggs. The maximum fecundity, egg diameter, and hatching rate were produced broodstock fed on 1.56% n-6 fatty acid and 0.10 % n-3 fatty acid in diet by at the level of 12.29% lipid.